The given equation is \(x^2 + 4x + 3 = 0\).
To complete the statements:
- The value of \(a\) is 1 (coefficient of \(x^2\)).
- The value of \(b\) is 4 (coefficient of \(x\)).
- The value of \(c\) is 3 (constant term).
To find one solution to the equation, we can factor it:
The equation can be factored as \((x + 1)(x + 3) = 0\).
Setting each factor equal to zero gives:
- \(x + 1 = 0 \rightarrow x = -1\)
- \(x + 3 = 0 \rightarrow x = -3\)
Therefore, one solution to the equation is -1 (you could also state -3 as another solution, but since only one is requested, we give -1).
So, the completed statements are:
- The value of \(a\) is 1.
- The value of \(b\) is 4.
- The value of \(c\) is 3.
- One solution to the equation is -1.